CASSAVA FIBER BIOGAS WITH DIFFERENT INOCULA AND CHEMICAL CHARACTERIZATION OF THE BIODIGESTED SUBSTRATES - Pallo-Chango, Ivan (2021)
The main objective of this research was to evaluate the biogas production from cassava fibers (Manihot esculenta Crantz) with different inocula and chemical characterization of the biodigested substrates. The treatments were distributed as follows: T . Cassava peel + water, T . Cassava + water central cylinder, T . 1 2 3 Cassava peel + central cylinder + water, T . Cassava peel + Bovine manure biodigestion inoculum, T . 4 5 Cassava central cylinder + Bovine manure biodigestion inoculum, T . Peel + cassava central cylinder + 6 Bovine manure biodigestion inoculum, T . Cassava peel + Physic nut seed cake biodigestion inoculum, T . 7 8 Cassava central cylinder + Physic nut seed cake biodigestion inoculum, T . Cassava peel + central 9 cylinder + Physic nut seed cake biodigestion inoculum, T . Cassava peel + pig manure biodigestion 10 inoculum, T . Cassava central cylinder + pig manure biodigestion inoculum, T . Peel + cassava central 11 12 cylinder + pig manure biodigestion inoculum. The production of biogas was determined daily. In addition, the measurement of CH and CO was carried out with the Orsat method. Physical and chemical 4 2 parameters of the biodigested substrates were analyzed. The biodigestion of the central cylinder of the cassava or of the bark using as inoculants the biodigestion of pine nut cake or bovine manure produces 71.67% of CH . Biodigested substrates contain macro and micronutrients with potential use in agriculture.